Stwierdzenie rysia Lynx lynx w Puszczy Białej na podstawie materiału z fotopułapki - Haidt, Andżelika (Leśne Prace Badawcze, 2022)
On the 21 st June 2021 at 10:17 PM, one lynx individual was recorded in the area of the Wyszków Forest District by a camera trap (Browning Spec Ops Advantage). The device was set up as part of a study on the behaviour of predators at the crossing of forest roads. The camera trap was one of nine devices operating in the area from June 1st, 2019 to September 30 th , 2021 (853 working days). The Wyszków Forest District is located in the Biała Forest between two known lynx populations in the Kampinos Forest and the Eastern Baltic population. This record is the first report of a lynx sighting in the Biała Forest north of the Bug river.